2007
DOI: 10.1089/sur.2006.032
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Analysis of a Nanocrystalline Silver-Coated Surgical Mesh

Abstract: The CM demonstrated significant bactericidal activity compared with UM. Nanocrystalline silver particles may decrease the incidence of postoperative prosthetic mesh infections and be useful as a coating for other prosthetic materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(79 citation statements)
references
References 23 publications
1
76
0
2
Order By: Relevance
“…And because of these results Ag nanoparticles have been incorporated into a number of pharmaceutical preparations and wound dressings. [22][23] Future development and incorporation of Ag nanoparticles as antimicrobial agents in pharmaceutical products will require close control of particle size, morphology and particle stability. Furthermore, bioinspired synthesis of Ag nanoparticles via plants avoids contaminating particles with harmful chemicals and solvents traditionally used in conventional chemical and physical methods.…”
Section: Introductionmentioning
confidence: 99%
“…And because of these results Ag nanoparticles have been incorporated into a number of pharmaceutical preparations and wound dressings. [22][23] Future development and incorporation of Ag nanoparticles as antimicrobial agents in pharmaceutical products will require close control of particle size, morphology and particle stability. Furthermore, bioinspired synthesis of Ag nanoparticles via plants avoids contaminating particles with harmful chemicals and solvents traditionally used in conventional chemical and physical methods.…”
Section: Introductionmentioning
confidence: 99%
“…In a study it was found that silver nanoparticles polypropylene mesh had significant bactericidal efficacy against S. aureus. Furthermore, it was shown that silver nanoparticles could continue to diffuse off the mesh and had sustained activity (Cohen et al, 2007). These results clearly warrant that silver nanoparticles-coated polypropylene mesh can decrease the prosthetic infection rate and the host inflammatory response in the clinical setting.…”
Section: Surgical Meshmentioning
confidence: 65%
“…Ultrahigh molecular weight polyethylene fabricated with silver nanoparticle are used in joint replacement components, the silver nanoparticle that reduces the wear and tear of the polyethylene polymer [37]. The surgical meshes that made of silver nanoparticle coated polypropylene are used as an ideal candidate for surgical meshes due to its antimicrobial, anti-inflammatory properties [38].…”
Section: Figure 2 Site Targeted Analysis Using Detector Dna Probe Tagmentioning
confidence: 99%